Wigner Distribution and Boltzmann-Shannon Entropy for a Diatomic Molecule under Polarized Electric Field Interaction II: A Recent Study - López, Gustavo V.; Mercado, Alejandro P. (Newest Updates in Physical Science Research Vol. 11, 2021)
We study the classical chaos appearing in a diatomic molecules BeO, CO and CN due to the interaction with a circularly polarized electric field, and its signature in Quantum Mechanics through the Wigner distribution function and the Boltzmann-Shannon entropy. We found a motion out of the center of the quantum phase space defined by Wigner function when the classical system becomes chaotic, and we found a jumping behavior of the average Boltzmann-Shannon entropy with respect the electric field strength when the classical system becomes chaotic, indicating a sudden increasing in the disorder (or sudden lost of information) in the quantum system. The analysis was to be able to do it further with the parameter Wc since much larger number of states have to be considered, but one could expect further increasing of the BS entropy since more state will be involved in the quantum dynamics.